Procoagulant Activity and Cytokine Expression in Whole Blood Cultures from Patients with Atherosclerosis Supplemented with Omega-3 Fatty Acids - Seljeflot, Ingebjørg; Johansen, Odd; Arnesen, Harald; Eggesbø, Jan-Bertil; Westvik, Åse-Britt; Kierulf, Peter (Thrombosis and Haemostasis, 1999)
Omega-3 fatty acids (n-3 FA) may reduce atherogenesis and thrombosis. We investigated the effects of n-3 FAs on procoagulant activity and cytokine expression in whole blood cultures from patients with atherosclerosis. Eleven of the 23 included patients had received 5.1 g n-3 FA daily for 6 months (group I) whereas 12 patients had been on placebo (group II). All patients were then given 5.1g n-3 FA daily for another 4 weeks.At baseline significantly lower levels of LPS-induced prothrombin fragment1+2 were found in group I (p = 0.010), this difference being eliminated after 4 weeks. Il-6 and TNFαwere significantly higher at baseline in group I and the differences in changes from baseline between the groups were statistically highly significant with increasing values in group II (Il-6 p = 0.001, TNFαp = 0.002).The present results indicate a reduction in pro-thrombotic potential in patients receiving highly concentrated n-3 FA, whereas some pro-inflammatory responses might be adverse.